Hypermarket Brand Extension Products and Service Experience - Hassan, Hasliza; Sabbir Rahman, Muhammad; Bakar Sade, Abu (International Journal of Engineering and Technology, 2018)
This cross-sectional research examines the acceptance of consumers in hypermarket brand extension products and the enhancement of service experience being offered by hypermarkets in Malaysia by exploring the data collected through descriptive and cross-tabulation analyses. The majority of consumers in Malaysia accept the hypermarket brand extension products and service experience that are being offered by the hypermarkets. The consumer purchases and consumes the hypermarket brand extension products and service experience concurrently. The findings from this research offer a significant outcome in which the hypermarket retailers should provide a wider variety of products and service experience as an additional option for the consumers to choose. It is expected that this research will provide a breakthrough to determine how far hypermarkets could extend the retail brand in both products and services, and how this effort could be beneficial to the stakeholders. The concept of integrated marketing is explored further in this study by looking at the integration of products and services to deliver greater consumer value.Â Â Â
Keywords: Brand Extension; Experience; Hypermarket; Product; Service; Shopping.